Problems of designing and using regional input-output models for Ireland, illustrated by 1974 numerical data - Henry, E. W. (Statistical and Social Inquiry Society of Ireland, 1978)
The main purposes of the following essay can be grouped under four headings: (i) to stimulate interest in the capabilities of regional models to provide useful information for planning, once numerous problems of compilation have been faced and solved and a satisfactory design chosen. (ii) to show how regional input-output models can complement the County Incomes' published researches of Miceal Ross (1971 and 1972) and the associated employment findings of Baker and Ross (1975). (iii) to draw attention to existing data lacunae, in the hope that statistical information might be Sought and provided as part of a thorough investigation of regional models, if such a project were undertaken. (iv) to illustrate the regional modelling ideas by way of a two-region model for 1974.
Read before the Society, 3 November 1977
Keywords: Regional input-output models; Economic planning; Regional economic models; 314.15